2023
DOI: 10.1186/s12889-023-16310-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends of underweight, overweight, and obesity among older adults in China from 2008 to 2018: a national observational survey

Abstract: Objective This study aims to investigate the 10-year trends and disparities in underweight, overweight, and obesity among older adults aged 65 years and older in China from 2008 to 2018. Methods We used four waves (2008, 2011, 2014, and 2018) of data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), a national community-based cross-sectional survey conducted every 2–3 years. Body weight and height were measured by trained assessors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…[3] Moreover, a national observational survey also revealed that the prevalence of overweight rose from 12.82% in 2008 to 28.45% in 2018, and the prevalence of obesity increased from 1.62% in 2008 to 4.95% in 2018. [4] Low physical activity levels, poor physical fitness, and obesity are the most common causes of reduced cerebral blood flow, premature death, along chronic non-communicable diseases for adolescents. [5,6] Core strength is crucial for injury prevention, enhancing body stability, regulating the center of gravity, and transmitting strength between the upper and lower limbs.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Moreover, a national observational survey also revealed that the prevalence of overweight rose from 12.82% in 2008 to 28.45% in 2018, and the prevalence of obesity increased from 1.62% in 2008 to 4.95% in 2018. [4] Low physical activity levels, poor physical fitness, and obesity are the most common causes of reduced cerebral blood flow, premature death, along chronic non-communicable diseases for adolescents. [5,6] Core strength is crucial for injury prevention, enhancing body stability, regulating the center of gravity, and transmitting strength between the upper and lower limbs.…”
Section: Introductionmentioning
confidence: 99%